Bronze Age and Early Iron Age house and settlement development at Forsandmoen, south-western Norway (AmS-Skrifter, 2020)
The ambition of this monograph is to analyse a limited number of topics regarding house types and thus social and economic change from the extensive material that came out of the archaeological excavation that took place at Forsandmoen (“Forsand plain”), Forsand municipality, Rogaland, Norway during the decade 1980–1990, as well as the years 1992, 1995 and 2007. The excavation was organised as an interdisciplinaryresearch project within archaeology, botany (palynological analysis from bogs and soils, macrofossil analysis) and phosphate analysis, conducted by staff from the Museum of Archaeology in Stavanger (as it was called until 2009, now part of the University of Stavanger). A large phosphate survey project had demarcaded a 20 ha settlement area, among which 9 ha were excavated using mechanical topsoil stripping to expose thehabitation traces at the top of the glaciofluvial outwash plain of Forsandmoen. A total of 248 houses could be identified by archaeological excavations, distributed among 17 house types. In addition, 26 partly excavated houses could not be classified into a type. The extensive house material comprises three types of longhouses, of which there are as many as 30–40 in number, as well as four other longhouse types, of which there are only 2–7 in number. There were nine other house types, comprising partly small dwelling houses and partly storage houses, of which there were 3–10 in number. Lastly, there are 63 of the smallest storage house, consisting of only four postholes in a square shape. A collection of 264 radiocarbon dates demonstrated that the settlement was established in the last part of the 15th century BC and faded out during the 7th–8th century AD, encompassing the Nordic Bronze Age and Early Iron Age. As a number of houses comprising four of the house types were excavated with the same methods in the same area by the same staff, it is a major goal of this monograph to analyse thoroughly the different featuresof the houses (postholes, wall remains, entrances, ditches, hearths, house-structure, find-distribution) and how they were combined and changed into the different house types through time. House material from different Norwegian areas as well as Sweden, Denmark, Germany and the Netherlands is included in comparative analyses to reveal connections within the Nordic area. Special attention has been given to theinterpretation of the location of activity areas in the dwelling and byre sections in the houses, as well as the life expectancy of the two main longhouse types. Based on these analyses, I have presented a synthesis in 13 phases of the development of the settlement from Bronze Age Period II to the Merovingian Period. This analysis shows that, from a restricted settlement consisting of one or two small farms in the Early BronzeAge, it increases slightly throughout the Late Bronze Age to 2–3 solitary farms to a significantly larger settlement consisting of 3–4 larger farms in the Pre-Roman Iron Age. From the beginning of the early Roman Iron Age, the settlement seems to increase to 8–9 even larger farms, and through the late Roman Iron Age, the settlement increases to 12–13 such farms, of which 6–7 farms are located so close together that they would seem to be a nucleated or village settlement. In the beginning of the Migration Period, there were 16–17 farms, each consisting of a dwelling/byre longhouse and a workshop, agglomerated in an area of 300 x 200 m where the farms are arranged in four E–W oriented rows. In addition, two farms were situated 140 m NE of the main settlement. At the transition to the Merovingian Period, radiocarbon dates show that all but two of the farms were suddenly abandoned. At the end of that period, the Forsandmoen settlement was completely abandoned. The abandonment could have been caused by a combination of circumstances such as overexploitation in agriculture, colder climate, the Plague of Justinian or the collapse of the redistributive chiefdom system due to the breakdown of the Roman Empire. The abrupt abandonment also coincides with a huge volcanic eruption or cosmic event that clouded the sun around the whole globe in AD 536–537. It is argued that the climatic effect on the agriculture at this latitude could induce such a serious famine that the settlement, in combination with the other possible causes, was virtually laid waste during the ensuing cold decade AD 537–546.